Revisiting An Islamic Approach to Humanities: A Critical Review - Sebastian Herman; Mohd Mahyudi bin Mohd Yusop (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: The study aims to develop a relevant counter-argument and supporting justification on ideas offered by Zaman (2014) in his paper titled